(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Naayuruvi Kuzhi thylam (NKT) is a Siddha single herbal formulation indicated in literature for the management of Asthma (Suvasa irumal ICD-DBA1.3)). Since asthma can accompany with other comorbid bacterial infections, the present study was focused to scientifically evaluate the antimicrobial action of Naayuruvi kuzhi thylam (NKT) against selected pathogens and also its chemical analysis. The antimicrobial action of Naayuruvi kuzhi thylam (NKT) was performed against selected bacterial and fungal pathogens such as Escherichia coli, Streptococcus aureus, Salmonella typhi and Candida albicans. Naayuruvi kuzhi thylam (NKT) was prepared and a concentration of 1000µg, 500µg, 250µg, 100µg of NKT was inoculated in the Agar well medium. The antibacterial activity of the given sample was determined by disc diffusion method on Muller Hinton agar (MHA) medium and the zone of inhibition was determined using the standard antibiotic Streptomycin 10µg as control. All the tested pathogens showed maximum zone of inhibition (8mm) at a concentration of 1000µg of NKT. The chemical analysis revealed the presence of phosphate, sulphide, Calcium, potassium, ammonium, alkaloid, starch and aminoacids. The results conclude that the study drug NKT possess intermediate antimicrobial activity against the selected pathogens.